Synthesis of 1,3,4-Oxadiazoles by Iodine-Mediated Oxidative Cyclization of Methyl Ketones with 4-Phenylsemicarbazide - Zhang, Shanshan; Liu, Chuang; Wu, Xiaojun; Li, Wen; Li, He; Wang, Shiwei; Leng, Yuting; Wu, Yangjie (Synlett, 2021)
An efficient one-pot method has been developed to access 5-amino-2-(het)aroyl-1,3,4-oxadiazoles through I2/DMSO-promoted oxidative cyclization of 4-phenylsemicarbazide with (het)aryl methyl ketones under mild conditions. This reaction proceeds smoothly with a wide range of methyl ketones containing various functional groups to give the corresponding products in moderate yields under mild conditions.
Keywords: one-pot reaction; oxadiazoles; oxidative cyclization; phenylsemicarbazide; methyl ketones